Cross-cultural adaptation and psychometric properties of the Arabic version of the Telerehabilitation Usability Questionnaire - Khalid H. Shebli; Fahad H. Alshehri; Yasir S. Alshehri; Yousef M. Alshehre; Rania N. Almeheyawi; Hosam Alzahrani (Annals of Medicine)
Background The objective of this study was to translate and cross‑culturally adapt the Telerehabilitation Usability Questionnaire (TUQ) into Arabic (TUQ-Arabic) and analyse the psychometric properties of the questionnaire.Patients and methods Translation and cross-cultural adaptation have been conducted following international guidelines. A cohort of 270 Arabic-speaking participants completed the TUQ-Arabic. This study included participants who had utilised telerehabilitation services. Internal consistency was assessed with Cronbach’s alpha coefficient. The test–re-test reliability was performed on 69 participants using the intraclass correlation coefficient (ICC).Results The cohort of the study comprised of 118 female (43.7%) and 152 male (56.3%) participants. Our findings indicate robust internal consistency in TUQ-Arabic subscales, exhibiting excellent Cronbach’s alpha values (>0.90, ranging from 0.902 to 0.940). The overall TUQ-Arabic score displayed excellent internal consistency (Cronbach’s alpha = 0.98). The test–re-test reliability of the total TUQ-Arabic score was excellent, with an ICC of 0.975 (95% CI 0.960–0.984, p < 0.001). Similarly, the test–re-test reliability of the TUQ-Arabic subscales ranged from good to excellent.Conclusion The TUQ-Arabic is internally consistent and reliable, paralleling the original TUQ. Participants displayed favourable views on the telerehabilitation services, resulting in high satisfaction. The TUQ-Arabic is suitable for assessing the usability of remote telerehabilitation services in Saudi Arabia and populations globally.